Determinants of pathways to care among young adults with early psychosis entering a coordinated specialty care program. Issue 5 (10th September 2019) - Marino, Leslie; Scodes, Jennifer; Ngo, Hong; Nossel, Ilana; Bello, Iruma; Wall, Melanie; Dixon, Lisa
Abstract: Aim: To describe the characteristics of the pathway to coordinated specialty care for young adults with early psychosis in the United States, to examine how various factors correlate with the duration of untreated psychosis (DUP), and to explore factors associated with time from onset of symptoms to first mental health service contact (help‐seeking DUP). Methods: The sample included 779 individuals ages 16 to 30 with recent‐onset non‐affective psychosis enrolled in OnTrackNY. Domains assessed included demographics, clinical characteristics, mental health service utilization and characteristics of the pathway to care. Primary outcomes included the time from onset of psychotic symptoms to admission to OnTrackNY (DUP) and time from onset of psychotic symptoms to first mental health service contact (help‐seeking DUP). Results: The mean DUP was 231.2 days (SD = 87.7, median = 169) and mean help‐seeking DUP was 73.7 days (SD = 110.8, median = 27). Being in school, better social functioning, and greater number of ER visits or hospitalizations were associated with shorter DUP. Violent ideation or behaviour and having an outpatient mental health visit as the first service contact or hallucinations as the reason for first service contact were significantly associated with longer DUP. Only the type of first service contact (outpatient mental health treatment or other non‐mental health service provider) and having hallucinations as the clinical reason for the first service contact were associated with help‐seeking DUP. Conclusions: Referral delays were longer than help‐seeking delays. Strategies to reduce treatment referral delays through systems‐level interventions may be most likely to reduce the overall DUP in this population.